2015
DOI: 10.5194/isprsarchives-xl-7-w3-617-2015
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Threshold Cloud Detecting Approach based on the Brightness Temperature from FY-2 VISSR Data

Abstract: THEME: DATA -Data and information systems and spatial data infrastructure.KEY WORDS: Cloud detecting, Brightness temperature, FY-2 VISSR data, Dynamic threshold, Temporal-Spatial scale ABSTRACT:The traditional statistical methods and radiation transfer theory methods for cloud detecting have a high adaptability just only in those areas with a uniform surface coverage and noncomplex terrain. Therefore, adapted to large spatial and temporal scales, in this work a cloud detection method is developed, seeking the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…These probabilities have been derived from hourly plots of normal distributions of ice and water pixels and applied to an ice detection algorithm that uses the mid-infrared band to delineate thick ice and water. Dynamic thresholds in the visible have been used in previous studies including ice mapping which has been demonstrated over the Caspian Sea [2] and in brightness temperature for cloud detection [12].…”
Section: Introductionmentioning
confidence: 99%
“…These probabilities have been derived from hourly plots of normal distributions of ice and water pixels and applied to an ice detection algorithm that uses the mid-infrared band to delineate thick ice and water. Dynamic thresholds in the visible have been used in previous studies including ice mapping which has been demonstrated over the Caspian Sea [2] and in brightness temperature for cloud detection [12].…”
Section: Introductionmentioning
confidence: 99%